Case Report: Repeated Stereotactic Radiotherapy of Recurrent Ventricular Tachycardia: Reasons, Feasibility, and Safety - Haskova, Jana; Peichl, Petr; Šramko, Marek; Cvek, Jakub; Knybel, Lukáš; Jiravský, Otakar; Neuwirth, Radek; Kautzner, Josef (Frontiers in Cardiovascular Medicine, 2022)
Stereotactic body radiotherapy (SBRT) has been reported as an attractive option for cases of failed catheter ablation of ventricular tachycardia (VT) in structural heart disease. However, even this strategy can fail for various reasons. For the first time, this case series describes three re-do cases of SBRT which were indicated for three different reasons. The purpose in the first case was the inaccuracy of the determination of the treatment volume by indirect comparison of the electroanatomical map and CT scan. A newly developed strategy of co-registration of both images allowed precise targeting of the substrate. In this case, the second treatment volume overlapped by 60% with the first one. The second reason for the re-do of SBRT was an unusual character of the substrate–large cardiac fibroma associated with different morphologies of VT from two locations around the tumor. The planned treatment volumes did not overlap. The third reason for repeated SBRT was the large intramural substrate in the setting of advanced heart failure. The first treatment volume targeted arrhythmias originating in the basal inferoseptal region, while the second SBRT was focused on adjacent basal septum without significant overlapping. Our observations suggested that SBRT for VT could be safely repeated in case of later arrhythmia recurrences (i.e., after at least 6 weeks). No acute toxicity was observed and in two cases, no side effects were observed during 32 and 22 months, respectively. To avoid re-do SBRT due to inaccurate targeting, the precise and reproducible strategy of substrate identification and co-registration with CT image should be used.